Morphological changes of the internal carotid artery: prevalence and characteristics. A clinical and ultrasonographic study in a series of 19 804 patients over 25 years old. (17th November 2017) - Martins, H. F. G.; Mayer, A.; Batista, P.; Soares, F.; Almeida, V.; Pedro, A. J.; Oliveira, V.
Abstract : Background and purpose: Morphological changes of the internal carotid arteries (McICA) are frequently found during cervical ultrasound studies. However, the etiology of McICA remains controversial. During this study, the prevalence and demographic characteristics of McICA, such as kinking, coiling or looping identified by Doppler ultrasound, were analysed and its relationship with vascular risk factors and stroke was assessed. Methods: A retrospective study was performed by analysing 19 804 patients who were subjected to cervical ultrasonographic study between January 2000 and June 2012. The data were statistically analysed with SPSS ® 20 and a multivariate logistic regression was performed. Statistical significance was accepted for P < 0.05 and 95% confidence intervals (CIs) were used. Results: Morphological changes of the internal carotid arteries were present in 2678 patients (13.5%) and were unilateral in 61.6% of these cases. Carotid kinking was found in 80% of the patients, coiling in 16% and looping in 1%. In multivariate analysis, the presence of McICA was related to older groups (1.04; 95% CI, 1.04–1.05; P < 0.01), female gender (1.78; 95% CI, 1.64–1.94; P < 0.01), patients with hyperlipidemia (1.28; 95% CI, 1.17–1.40; P < 0.01), carotid thickness (1.22; 95% CI, 1.13–1.33; P < 0.01) and cardiac or cardioembolic disease (1.11; 95% CI, 1.01–1.21; P = 0.02). The results of this study indicate that kinking in the carotid artery was associated with ipsilateral cerebral ischemic events (1.43; 95% CI, 1.040–1.958; P < 0.05). Conclusion: Morphological changes of the internal carotid arteries were associated with aging, female gender and patients with hyperlipidemia, hypertension, diabetes and heart disease. Kinking was associated with ipsilateral cerebral ischemia.